Extreme solutions of nonlinear, second order integro-differential equations in Banach spaces. (1995) - Guo, Dajun
Abstract : After establishing a comparison result by means of a new method, we obtain the existence of maximal and minimal solutions for nonlinear, second order integro-differential equations of mixed type in Banach spaces.